Analysis of suitability of material aspects in articulate storylane based solution colligative learning media for PGSD students - Wahyudi; Amirul Mukmin, Bagus; Sahari, Sutrisno; Salsabela, Qonita (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
This study aims to determine the suitability of colligative material aspects of the solution in articulate storyline-based learning media with assessment indicators on aspects of suitability of material with Basic Competency, suitability of material concepts with media, contextuality, depth of material, ease of material to understand, systematics, clarity of material, suitability of amount practice questions with the amount of material presented, the ease of reviewing the material, motivating students as a whole. The research instrument was a questionnaire assessment sheet related to the suitability of the material with the Basic Competency in articulate storyline-based learning media based on the aspects that have been mentioned. The method used in this study is the one method, which is a research step using a qualitative approach. The results of the research on the suitability analysis of colligative material solutions on articulate storyline-based learning media were obtained from a validity questionnaire questionnaire by two material experts. The suitability of the material aspects of this media is the result of validator one giving an average score with a percentage score of 88% including very good criteria (very valid), and validator two giving a percentage of an average score of 82%, namely in the good category ( valid). So it can be concluded that the suitability of the material aspects of the articulate storyline-based learning media is stated to be appropriate and valid